Justification for improving the design of a freezer for ice cream production - Liebiediev, A. (Запоріжжя: ТДАТУ, 2026)
Ice cream is a frozen dessert product manufactured primarily from milk, cream, butterfat, and sugar, with the addition of flavoring and aromatic components. In addition to traditional dairy-based , ice cream may also be produced in fruit varieties formulated from fruit juices and pulp derived from berries and other fruits. As a dairy product, ice cream contains more than one hundred biologically valuable constituents. Its composition includes proteins, lipids, carbohydrates, and a complex of vitamins such as A, B₁, B₂, B₁₂, C, D, E, and P. The concentration of vitamin C increases when fruit fillers are incorporated into the formulation. The ingredients of ice cream contribute to the synthesis of serotonin in the human body. Milk-based ice cream is also characterized by a significant content of tryptophan, a natural compound known for its mild calming effect.
Keywords: ice cream; frozen dessert product